Microdroplet fusion mass spectrometry: accelerated kinetics of acid-induced chlorophyll demetallation. (1st February 2017) - Lee, Jae Kyoo; Nam, Hong Gil; Zare, Richard N.
Abstract: Kinetics of acid-induced chlorophyll demetallation was recorded in microdroplets by fusing a stream of microdroplets containing 40 µM chlorophyll a or b dissolved in methanol with a stream of aqueous microdroplets containing 35 mM hydrochloric acid (pH = 1·46). The kinetics of the demetallation of chlorophyll in the fused microdroplets (14 ± 6 µm diameter; 84 ± 18 m s −1 velocity) was recorded by controlling the traveling distance of the fused microdroplets between the fusion region and the inlet of a mass spectrometer. The rate of acid-induced chlorophyll demetallation was about 960 ± 120 times faster in the charged microdroplets compared with that reported in bulk solution. If no voltage was applied to the sprayed microdroplets, then the acceleration factor was about 580 ± 90, suggesting that the applied voltage is not a major factor determining the acceleration. Chlorophyll a was more rapidly demetallated than chlorophyll b by a factor of ~26 in bulk solution and ~5 in charged microdroplets. The demetallation kinetics was second order in the H + concentration, but the acceleration factor of microdroplets compared with bulk solution appeared to be unchanged in going from pH = 1·3 to 7·0. The water:methanol ratio of the fused microdroplets was varied from 7:3 to 3:7 causing an increase in the reaction rate of chlorophyll a demetallation by 20%. This observation demonstrates that the solvent composition, which has different evaporation rates, does not significantly affect the acceleration. We believe that a major portion of the acceleration can be attributed to confinement effects involving surface reactions rather than either to evaporation of solvents or to the introduction of charges to the microdroplets.